Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Produk Listrik Prabayar Di Pt.Pln (Persero) Gresik - Fitroh Tri Kurnia Maulidina; Budiyono Pristyadi (Jurnal Mahasiswa Manajemen, 2020)
This study aims to analyze the influence of service quality (direct evidence, reliability, responsiveness, assurance and concern) on the satisfaction of prepaid electricity customers at PT PLN (Persero) Gresik, case study: Ngipik Village, Gresik District. This study uses a quantitative approach. the subject of this study was prepaid electricity customers of PT. PLN (Persero) Gresik, with 120 samples. Data analysis techniques used are multiple linear regression analysis. The regression results obtained t count of 3.571 while the t table amounted to 1.980 which means direct evidence has an effect on customer satisfaction at PT. PLN (Persero) Gresik. Reliability variable has t count of 2.856 while t table is 1.980, therefore the reliability variable influences customer satisfaction at PT. PLN (Persero) Gresik. The responsiveness variable has a t count of 2.696 while the t table is 1.980 so the responsiveness variable influences customer satisfaction at PT. PLN (Persero) Gresik. The guarantee variable has a t count of 3.039 while the t table is 1.980 so the guarantee variable influences customer satisfaction at PT. PLN (Persero) Gresik. Concern variables have t arithmetic of 3.410 while t table is 1.980 so that the variables of concern affect customer satisfaction at PT. PLN (Persero) Gresik. direct evidence variables, reliability, responsiveness, assurance and concern have a simultaneous and significant effect on customer satisfaction.